Ulipristal acetate therapy increases ultrasound features of adenomyosis: a good treatment given in an erroneous diagnosis of uterine fibroids. (4th March 2019) - Conway, Francesca; Morosetti, Giulia; Camilli, Sara; Martire, Francesco Giuseppe; Sorrenti, Giuseppe; Piccione, Emilio; Zupi, Errico; Exacoustos, Caterina
Abstract: Ulipristal acetate (UPA) is used for medical treatment of uterine fibroids. The aim of this study was to describe the effects on painful symptoms and the sonographic uterine modifications in patients with adenomyosis erroneously treated with UPA. This is an observational study on six women affected by adenomyosis and treated with three months of UPA (5 mg/24h). The baseline ultrasonography (US) was not performed at out center nor was the diagnosis of fibroids. The patients came to our attention after the treatment with UPA, prescribed by an external physician. During our post-treatment scan we found aspects of adenomyosis, while no fibroids were detected. Symptoms, myometrial and endometrial ultrasound features were evaluated. All patients reported an increase in pelvic pain. At US evaluation intramyometrial cystic areas were found in all six cases (100%). All patients showed an enhancement of adenomyosis features.The intra-myometrial cysts appeared enlarged and the vascularization enhanced when compared to the images of the pretreatment scan. In patients with adenomyosis treated with UPA due to an erroneous diagnosis of uterine fibroids we observed a worsening of the US features of adenomyosis and of the painful symptoms.